Social reproduction theory : remapping class, recentering oppression - Bhattacharya, Tithi; Vogel, Lise (London : Pluto Press, 2017)
How do childcare, healthcare, education, family life and the roles of gender, race and sexuality affect our lives under capitalism?
Introduction: Mapping social reproduction theory / Tithi Bhattacharya -- Crisis of care? On the social-reproductive contradictions of contemporary capitalism / Nancy Fraser -- Without reserves / Salar Mohandesi and Emma Teitelman -- How not to skip class: social reproduction of labor and the global working class / Tithi Bhattacharya -- Intersections and dialectics: critical reconstructions in social reproduction theory / David McNally -- Children, childhood and capitalism: a social reproduction perspective/ Susan Ferguson -- Mostly work, little play: social reproduction, migration, and paid domestic work in Montreal / Carmen Teeple Hopkins -- Pensins and social reproduction / Serap Saritas Oran -- Body politics: the social reproduction of sexualities / Alan Sears -- From social reproduction feminism to the women's strike / Cinzia Arruzza
Includes bibliographical references (pages 197-240) and index.
Description based on print version record; title from digital title page (viewed September 27, 2023).
eBooks on EBSCOhost
Keywords: Capitalism -- Social aspects; Consumption (Economics) -- Social aspects; Social capital (Sociology); Social problems; Communism; Social Problems; Capital social (Sociologie); Problèmes sociaux; Société de consommation -- Aspect social; social issues; SOCIAL SCIENCE -- Feminism & Feminist Theory; Capitalism -- Social aspects; Communism; Consumption (Economics) -- Social aspects; Social capital (Sociology); Social problems; Electronic book